A novel smart coating with hexacyanoferrate intercalated layered double hydroxides nanoadditive for early detection of carbon steel corrosion - Sushkova, Alesia; Montes, Rodrigo; Paulino, Tiago; Sousa, Isabel; Neves, Cristina; Ferreira, Mário G. S.; Tedim, João (Frontiers in Chemical Engineering, 2023)
The detection of corrosion at early stages could increase the service life of metal-based infrastructures in a cost-effective manner. Despite the recent progress in “smart” self-reporting corrosion sensing coatings, the development of environmentally friendly systems appropriate for steel substrate used in offshore applications remains a relevant challenge. In this study, a novel smart corrosion sensing coating, based on hexacyanoferrate intercalated Mg-Al LDH nanoadditive, was developed, aiming at the detection of early-stage corrosion of carbon steel. The detection mechanism is based on the ability of hexacyanoferrate ions to react with iron cations generated during the corrosion process, giving rise to a colorimetric signal, while LDH carriers provide a controlled release of active ions under corrosion conditions. The sensing nanoadditive was embedded into a commercial pigment-free water-based acrylic polyurethane coating. The nanomaterial was characterized structurally (XRD) and morphologically (STEM). The compatibility of the additive with the polymer formulation and its influence on the resulting coating performance was investigated in terms of rheological behavior, structure (FTIR), morphology (SEM/EDS), thermal (TGA, DSC) and mechanical (adhesion, hardness) properties. The corrosion protection ability of the coating was evaluated via EIS, while the sensing functionality was analyzed by visual analysis of the surface. The developed coating successfully detects early-stage corrosion of steel substrate at a lab scale, in conditions relevant to the use of metallic structures in offshore applications, demonstrating a correlation between the level of material degradation and the spectroscopic signal associated with the presence of the LDH functional nanoadditive. Subsequently, a multilayer coating system with an additional protective layer without additives was developed, to increase barrier effect against ingress of aggressive species. Two different topcoats (epoxy- and polyurethane-based) were surveyed for this purpose, showing an improvement in the coating barrier properties without influencing the corrosion detection functionality of the sensing coating. The results were validated by standard salt spray tests.